2021
DOI: 10.3389/fvets.2021.645221
|View full text |Cite
|
Sign up to set email alerts
|

A Focus Group Study of Canadian Dairy Farmers' Attitudes and Social Referents on Antimicrobial Use and Antimicrobial Resistance

Abstract: As part of broader actions to combat antimicrobial resistance (AMR), health authorities have promoted the reduction of antimicrobial use (AMU) in food animals. Farmers' attitudes and receptivity to reduction of AMU appear to be variable and context specific. Our research objectives were to gain insight into Canadian dairy farmers' attitudes toward AMU, AMR, and AMU-reduction in the dairy industry, and to explore drivers and barriers to change AMU, including the influence of social referents. We conducted seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
6
15
0
Order By: Relevance
“…These results slightly contradict a 2019 study of a geographically similar population (New York dairy farmers), in which surveyed farmers indicated that two out of the top three motivating attributes for using antibiotics prudently were “increased profitability” and “decreased risk of residues”, respectively [ 22 ]. However, our results do support the results of a 2021 focus group study of Canadian dairy farmers, who frequently cited severity of clinical signs in their animals as a factor in whether they should treat with antibiotics or wait, and were more likely to treat empirically than wait if the animal was febrile, for example [ 23 ].…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…These results slightly contradict a 2019 study of a geographically similar population (New York dairy farmers), in which surveyed farmers indicated that two out of the top three motivating attributes for using antibiotics prudently were “increased profitability” and “decreased risk of residues”, respectively [ 22 ]. However, our results do support the results of a 2021 focus group study of Canadian dairy farmers, who frequently cited severity of clinical signs in their animals as a factor in whether they should treat with antibiotics or wait, and were more likely to treat empirically than wait if the animal was febrile, for example [ 23 ].…”
Section: Resultssupporting
confidence: 77%
“…The two heatmaps in Figure 1 and Figure 2 (for Q19 and Q21, respectively) suggest that dairy farmers’ and managers’ decisions to use or not use antibiotics are primarily based on keeping their cattle healthy, and other factors, such as cost or labor limitations, or limiting their antibiotic use are not as important. This supports the 2021 Canadian dairy farmer study, which found that farmers felt that cattle welfare is their responsibility, and they are not willing to jeopardize that by reducing antibiotic use [ 23 ]. Given that dairy cattle usually represent the entire livelihood of dairy farmers/managers, it is unsurprising that they find keeping their cattle healthy and free of disease very important and feel that utilizing antibiotics to help in this regard is appropriate.…”
Section: Resultssupporting
confidence: 74%
“…We did not ask how often producers actually referred to or followed their treatment protocols. Studies have suggested that calf caretakers may not follow the treatment protocols and may make decisions based on their experience or deviate from the treatment protocols to adjust for specific cases with severe clinical signs (Webb et al, 2019;Cobo-Angel et al, 2021;Okello et al, 2021). It is unclear whether deviations from a written treatment protocol relate to more or less usage of antimicrobials and to outcomes for calf health, which should be studied in the future.…”
mentioning
confidence: 99%
“…For some conditions such as cow lameness, mastitis, metritis, endometritis, and scours in calves, the respondents were less likely to seek veterinary medical advice (Fig 1 and 3). A study in Canada found that farmers used previous experiences of similar cases they encountered and the type of AMU as a determinant of the type of antimicrobial they were going to use when a similar case came up [35]. This may suggest either those farmers have a fair experience in dealing with clinical mastitis or that they have had consistent advice from their veterinarians on how to manage the disease impact on their cattle herds.…”
Section: Discussionmentioning
confidence: 99%